2009
DOI: 10.1007/978-3-642-00958-7_24
|View full text |Cite
|
Sign up to set email alerts
|

Graded-Inclusion-Based Information Retrieval Systems

Abstract: Abstract. This paper investigates the use of fuzzy logic mechanisms coming from the database community, namely graded inclusions, to model the information retrieval process. In this framework, documents and queries are represented by fuzzy sets, which are paired with operations like fuzzy implications and T-norms. Through different experiments, it is shown that only some among the wide range of fuzzy operations are relevant for information retrieval. When appropriate settings are chosen, it is possible to mimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…This point has been experimentally verified: experiments in [3] have shown that R-implications can give good results only when weights are chosen such that the thresholds are never reached.…”
Section: Threshold and R-implicationsmentioning
confidence: 80%
See 4 more Smart Citations
“…This point has been experimentally verified: experiments in [3] have shown that R-implications can give good results only when weights are chosen such that the thresholds are never reached.…”
Section: Threshold and R-implicationsmentioning
confidence: 80%
“…An IR system, founded on this fuzzy model has been implemented and tested on different standard collections of documents [3,14]. It was parametrized using a terms weighting scheme adapted from the one in BM25 (which is one of the best), normalized to fit properties of membership degrees.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations